A novel method to predict and prevent commutation failures in LCC-HVDC systems. (January 2023) - Zhou, Bohao; Li, Fengting; Yin, Chunya
Highlights: Commutation failures prediction and prevention (CFPP) strategy. High voltage direct current (HVDC). Line-commuted converter (LCC). Abstract: Commutation failures are the main drawbacks of the line-commutated converter-based high-voltage direct-current transmission systems. In this paper, the influences of the fault occurring moment on the commutation process are investigated quantitatively to predict and prevent commutation failures effectively. Then, the critical fault voltage and extinction angle calculation methods are presented based on the voltage–time area theory. The concept of the commutation failure domain and the security domain is determined to estimate the probability of commutation failures. Furthermore, the direct current and RMS voltage calculation methods under asymmetrical faults are presented. Based on them, we eventually propose a novel commutation failure prediction and prevention strategy. Compared with conventional methods, the proposed strategy takes account of the probabilistic characteristic of commutation failures. Moreover, the direct current is predicted rather than real-time measured, and the RMS voltage under asymmetrical faults can be calculated instantaneously. Therefore, the proposed strategy can obtain a rapid response and a stronger commutation failure immunity. The accuracy of the method proposed in this paper is validated by EMT results with PSCAD/EMTDC and the experimental results with RTDS.